2011
DOI: 10.4304/jltr.2.6.1252-1258
|View full text |Cite
|
Sign up to set email alerts
|

Learning Vocabulary via Mobile Phone: Persian EFL Learners in Focus

Abstract: Abstract-With encompassing power of cell phones and potentials of mobile learning for language teaching/learning, employing cell phones in language learning seems indispensable. Through exploiting the inherent capabilities of such devices this study investigated the efficacy of multimodal representation of L2 vocabularies for 158 pre-intermediate level L2 learners aged 18-23. Since short-term memory plays an important role in vocabulary learning, they were placed into four different short-term memory (STM) abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…The results of the present study also support those of Taki and Khazaei (2011) who investigated the use of mobile phone to present vocabulary in written and pictorial forms. The findings showed that the participants who used mobile phone applications performed better when they studied word with pictorial or written annotations.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results of the present study also support those of Taki and Khazaei (2011) who investigated the use of mobile phone to present vocabulary in written and pictorial forms. The findings showed that the participants who used mobile phone applications performed better when they studied word with pictorial or written annotations.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, mobile messaging applications have also been utilized to improve students' progress in learning different language skills and sub-skills consisting vocabulary, pronunciation, grammar, reading and listening (Alsaleem, 2014;Taki & Khazaei, 2011). Different mobile messaging applications have been examined to be implemented on students, but the effect of WhatsApp on vocabulary learning of Iranian EFL students has not been examined a lot.…”
Section: Introductionmentioning
confidence: 99%
“…The United Nations reported that, as of 2010, some 4.6 billion people are now mobile phone subscribers (Taki & Khazaei, 2011). While many of those subscribers may be using older devices that are not as suitable for education purposes, particularly in developing nations, it is expected that most of these subscribers will upgrade to more advanced devices as the technology continues to progress and become more affordable.…”
Section: Introductionmentioning
confidence: 99%
“…Some learners remember things better if they write them down, others make use of pictures to aid their memory, and some students may need more explanation than others. In this regard, multimedia technology can function as a facilitator in the process of language learning (Taki & Khazaei, 2011). When integrating this multimedia, education apps should be straightforward and easy to use (Cortez & Roy, 2012), as well as enjoyable.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the such drawbacks, we considered the entries generated by participants in a free-recall knowledge assessment [Wilson and Wilson 2013]. We argue that during an information search task, if users encounter the topically relevant words which are new to them, then they will be able to reproduce (at least some of) these words during a free recall assessment [Cooper and Pantle 1967;Feigenbaum 1961;Peterson and Peterson 1959;Taki and Khazaei 2011]. We counted the entries in the Pre-and Post-task responses, and analyzed the rank of the nouns used in them.…”
Section: Knowledge-change (Kc) Measuresmentioning
confidence: 99%